The pragmatic function of intonation in English and Slovene - Komar, Smiljana (Acta neophilologica, 2006)
The article examines the pragmatic role of intonation whose prime function is to enable the hearer to make inferences from the utterancećs context in order to enrich the interpretation. Intonation does not alter the sense of lexical items. Instead it provides the hearer with an opportunity to choose between different interpretations at the lexico-syntactic level. The intonation systems of different European languages exhibit quite a large number of similarities regarding the pragmatic role of intonation. The analysis of the communicative functions of tone, key and termination in English and Slovene was an attempt to prove the hypothesis of natural, iconic meanings of intonation.
Keywords: angleščina; English; intonacija; Slovene; slovenščina